Realization by the Children's Parents of Their Right to Freedom of Movement - V. Yu. Yevko (Bulletin of Kharkiv National University of Internal Affairs)
The subject matter of the work is the current legislation of Ukraine on the right to freedom of movement and the practice of its application. At present, the mechanism for parents to exercise their child’s right to freedom of movement is primarily designed to ensure the right of parents and children to communicate freely with each other. However, it somewhat restricts the child’s right to freedom of movement. Judicial practice demonstrates that cases of granting permission for temporary departure of a child abroad without the consent of the father (mother) and cases of returning the child to permanent residence in Ukraine are often decided by courts without taking into account the interests of the child. The purpose of the research is to analyze the current legislation of Ukraine, which establishes the mechanism for exercising the child’s right to freedom of movement by his parents and the practice of its application. The author of the article for the first time has studied and analyzed the main aspects of the mechanism of exercising the child’s right to freedom of movement. Based on a consistent analysis, the author has elaborated recommendations to eliminate differences in the current regulatory acts, the norms of which establish the mechanism for exercising the child’s right to freedom of movement, in order to avoid unjustified restrictions on this right.